2022
DOI: 10.1021/acsami.1c19412
|View full text |Cite
|
Sign up to set email alerts
|

Electroreduction of Nitrate to Ammonia on Palladium–Cobalt–Oxygen Nanowire Arrays

Abstract: Developing high-efficiency electrocatalysts for the selective reduction of nitrate to valuable ammonia is of great significance. Herein, Pd–PdO-modified Co3O4 nanowire arrays on nickel foam (PdCoO/NF) are fabricated by a facile cation-exchange reaction. Pd and PdO can facilitate the generation of adsorbed hydrogen, and abundant oxygen vacancies can promote nitrate activation. Therefore, the PdCoO/NF exhibits a superior nitrate conversion rate (89.3%), Faradaic efficiency (88.6%), and ammonium selectivity (95.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…The hydrogen atoms [H], produced from water electrolysis, are readily adsorbed on the Pd surface, facilitating reduction of nitrite to ammonia. 73,74 However, the stability and cost associated with the preparation of bimetallic particles should be assessed prior to the application of this technology. Compared to other plate-in-tank reactors (using a typical Hcell with complicated expensive electrocatalysts), the packed flowable cathode reactor described here using cost-effective copper-modified activated carbon exhibits excellent electrochemical stability and reusability and achieves high R NOd S7 for comparison).…”
Section: Environmental Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrogen atoms [H], produced from water electrolysis, are readily adsorbed on the Pd surface, facilitating reduction of nitrite to ammonia. 73,74 However, the stability and cost associated with the preparation of bimetallic particles should be assessed prior to the application of this technology. Compared to other plate-in-tank reactors (using a typical Hcell with complicated expensive electrocatalysts), the packed flowable cathode reactor described here using cost-effective copper-modified activated carbon exhibits excellent electrochemical stability and reusability and achieves high R NOd S7 for comparison).…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…While absorbed NO 3 – is reduced to NO 2 – on the Cu surface, subsequent reduction of NO 2 – to NH 4 + is facilitated via an adsorbed-hydrogen­([H])-mediated pathway on the Pd surface. The hydrogen atoms [H], produced from water electrolysis, are readily adsorbed on the Pd surface, facilitating reduction of nitrite to ammonia. , However, the stability and cost associated with the preparation of bimetallic particles should be assessed prior to the application of this technology. Compared to other plate-in-tank reactors (using a typical H-cell with complicated expensive electrocatalysts), the packed flowable cathode reactor described here using cost-effective copper-modified activated carbon exhibits excellent electrochemical stability and reusability and achieves high R NO 3 – ‑N , S NH 4 + ‑N , and R NH 4 + ‑N at a low cell voltage and comparable energy consumption to that achieved with other electrochemical technologies (see SI Table S7 for comparison).…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…[ 47,48 ] In addition, the peak in O 1s spectra in Figure S3c (Supporting Information) can be divided into two peaks that belong to hydroxyl species (O1, 531.5 eV) and chemisorbed water (O2, 532.6 eV). [ 49–51 ] It is obvious that the hydroxyl species are the most prevalent kind of oxygen, which supports the in situ introduction of Ni element even more. [ 52,53 ] These results confirm that a loading amount of active elements is present in Pd/NF.…”
Section: Resultsmentioning
confidence: 99%
“…The linear sweep voltammetry (LSV) curves show that the current density of both NF and Pd/NF samples in Figure 3b enhances significantly when 0.1 m NO 3 − ‐N was added into the electrolyte, demonstrating that the NO 3 − is involved in the reaction. [ 49,54 ] Moreover, the LSV curves for Pd/NF and NF tested in 0.5 m Na 2 SO 4 with 0.1 m NaNO 3 solution indicate that the loading of Pd can promote the reduction of NO 3 − . [ 55 ] In addition, the LSV curves for more Pd/NF samples under different Pd 2+ precursor concentrations are shown in Figure S4 (Supporting Information), indicating that the current density increases with the Pd 2+ precursor concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, both experiments and theoretical calculations have suggested that noble-metal materials (Pt, Pd, Ru, and Rh) are promising electrocatalysts for the NO 3 − RR under ambient conditions, as listed in Table 1. 20,38–42,45–48,50,52 For example, Li et al 42 designed Ru/oxygen-doped Ru core/shell nanoclusters (Fig. 2a and b) as an NO 3 − RR electrocatalyst for the production of NH 3 , in which the introduction of oxygen can increase the size of the Ru unit cell to induce tensile strains (Fig.…”
Section: Efficient No3−rr Electrocatalystsmentioning
confidence: 99%